2016
DOI: 10.1080/00952990.2016.1181179
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported use of novel psychoactive substances among attendees of electronic dance music venues

Abstract: Background Novel psychoactive substances (NPSs) continue to emerge in the United States and worldwide. Few epidemiological studies have examined the prevalence and correlates of use. Objective We examined the extent of NPS use in a high-risk population—attendees of electronic dance music (EDM) parties at nightclubs and festivals. Methods We surveyed 682 adults (age 18–25) entering EDM events at nightclubs and festivals in New York City (NYC) in 2015. A variation of time–space sampling was used. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…These results add to and corroborate a previous hair study which found higher levels of party attendance are related to a higher risk of testing positive for synthetic cathinones (Palamar, Salomone, et al, 2016). These results also corroborate multiple previous studies that have found higher levels of party attendance are related to robust increases in risk of using a variety of drugs including synthetic cathinones and other NPS (Palamar, Acosta, Ompad, et al, 2016; Palamar, Acosta, Sherman, et al, 2016; Palamar, Barratt, et al, 2016; Palamar et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results add to and corroborate a previous hair study which found higher levels of party attendance are related to a higher risk of testing positive for synthetic cathinones (Palamar, Salomone, et al, 2016). These results also corroborate multiple previous studies that have found higher levels of party attendance are related to robust increases in risk of using a variety of drugs including synthetic cathinones and other NPS (Palamar, Acosta, Ompad, et al, 2016; Palamar, Acosta, Sherman, et al, 2016; Palamar, Barratt, et al, 2016; Palamar et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
“…Parties were randomly selected using time-space sampling (MacKellar et al, 2007; Palamar, Acosta, Sherman, Ompad, & Cleland, 2016). Individuals were eligible if they 1) were about to attend the selected party and 2) identified as age 18-40.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study of EDM festival attendees found that among those who had reported using ecstasy within the last week, a number of their urine samples tested positive for “bath salts” such as alpha-PVP (“Flakka”) (12.5%), butylone (5.8%), ethylone (8.7%), dimethylone (9.6%), or methylone (22.1%) (Mohr et al, 2015). A more recent study of nightclub and dance festival attending young adults reporting lifetime ecstasy/MDMA/Molly use (and no use of “bath salts”), found that four out of ten who provided a hair sample for analysis tested positive for “bath salts” or other NPS (Palamar, Salomone, et al, 2016). Therefore, a number of ecstasy users in the US may in fact be unintentionally or unknowingly using potentially more dangerous NPS with—or in replacement of—ecstasy.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is also needed to examine characteristics of NPS users (who use intentionally) and according to whether or not they use ecstasy. While we have begun to investigate characteristics of NPS-using nightclub attendees (Palamar, Acosta, Sherman, Ompad, & Cleland, 2016), further investigation is needed to determine distinguishing factors among users.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased regulation, use of novel psychoactive substances (NPS) remains a prominent component of global drug culture and is especially popular among club- and rave-goers (Palamar et al, 2015; 2016a; 2016b). In addition to voluntary use, many individuals have inadvertently taken NPS as adulterants in “Ecstasy” or “Molly” formulations (UNODC, 2014; Palamar, 2016c).…”
Section: Introductionmentioning
confidence: 99%